Horace Kallen confronts America : Jewish identity, science, and secularism - Kaufman, Matthew J. (Modern Jewish history., 2019)
"During his more than fifty-year writing and teaching career, Horace M. Kallen (1882-1974), the American Jewish philosopher who coined the term "cultural pluralism," incorporated into his pragmatism-infused philosophy of life a number of different sciences, from racial science to psychology and physics. Part biography, part cultural history, "Horace Kallen Confronts America" offers fresh insight into the larger question of how social discourses shape modern American Jewish identity."--